Butyrate: a bridge between intestinal flora and rheumatoid arthritis - Cao, Yang; Chen, Jingjing; Xiao, Jing; Hong, Yujie; Xu, Ke; Zhu, Yan (Frontiers in Immunology, 2024)
In patients with rheumatoid arthritis (RA), intestinal flora imbalance and butyrate metabolism disorders precede clinical arthritis and are associated with the pathogenesis of RA. This imbalance can alter the immunology and intestinal permeability of the intestinal mucosa, leading to damage to the intestinal barrier. In this context, bacteria and their metabolites can enter the bloodstream and reach the distant target tissues of the host, resulting in local inflammation and aggravating arthritis. Additionally, arthritis is also exacerbated by bone destruction and immune tolerance due to disturbed differentiation of osteoclasts and adaptive immune cells. Of note, butyrate is a metabolite of intestinal flora, which not only locally inhibits intestinal immunity and targets zonulin and tight junction proteins to alleviate intestinal barrier-mediated arthritis but also inhibits osteoclasts and autoantibodies and balances the immune responses of T and B lymphocytes throughout the body to repress bone erosion and inflammation. Therefore, butyrate is a key intermediate linking intestinal flora to the host. As a result, restoring the butyrate-producing capacity of intestinal flora and using exogenous butyrate are potential therapeutic strategies for RA in the future.